2005
DOI: 10.1007/s00268-005-7687-2
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of Surgical Treatment for Pulmonary Metastasis from Hepatocellular Carcinoma

Abstract: The outcome of pulmonary metastasectomy of hepatocellular carcinoma (HCC) was appraised in this study. Twenty patients with pulmonary metastasis from HCCs undergoing pulmonary resection between 1990 and 2003 were included in this study. They had undergone curative treatment for the primary lesion and were candidates for a pulmonary metastasectomy for complete resection. Among the 20 patients, 13 died: 5 from hepatic failure, 5 from respiratory failure, and 2 from brain metastasis due to recurrence of the HCC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 16 publications
4
41
3
Order By: Relevance
“…Two of our patients were submitted to a vertebral body resection of a metastasis of HCC in the spine with survival of more than 1 year in one. A few previous reports suggested that resection of an isolated metastasis in the lung, 11,12,14 adrenal gland, 30 peritoneal cavity, 31 and abdominal wall 32 may result in long-term survival in selected patients. A recent study demonstrated that resection of an isolated extrahepatic recurrence might offer long-term survival.…”
Section: Treatment Of Extrahepatic Recurrencementioning
confidence: 99%
“…Two of our patients were submitted to a vertebral body resection of a metastasis of HCC in the spine with survival of more than 1 year in one. A few previous reports suggested that resection of an isolated metastasis in the lung, 11,12,14 adrenal gland, 30 peritoneal cavity, 31 and abdominal wall 32 may result in long-term survival in selected patients. A recent study demonstrated that resection of an isolated extrahepatic recurrence might offer long-term survival.…”
Section: Treatment Of Extrahepatic Recurrencementioning
confidence: 99%
“…4) Pulmonary metastasectomy for pulmonary metastasis of HCC has been reported to play an important role in selected patients, particularly in those with a limited number of pulmonary metastases, unilateral metastases, or requiring single pulmonary surgery. [5][6][7] Sorafenib is the first drug that has been shown to be effective for patients with advanced hepatocellular carcinoma. 8) Our patient was administered sorafenib due to the presence of pulmonary metastases and a mediastinal lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In the view of cardiology, the possibility of heart failure and pulmonary embolism increased rapidly when intra-cardiac mass size exceeded 1 cm 3 [2][3][4][5][6] . HCC with cardiac involvement always has malignant presentation and the worst outcome.…”
Section: B Amentioning
confidence: 99%
“…Finally, it is important to note some limitations to the current review. First, data about non-bypass cardiac surgery or simultaneous resection of main tumor and cardiac metastatic tumor, or concurrent resection of pulmonary metastasis [4][5][6] remain unavailable, but these improved surgical techniques may offer better results for advanced HCC patients with cardiac involvement. Second, this study only considers retrospective results, but a prospective study or more data may be necessary to confirm the longterm mortality.…”
Section: B Amentioning
confidence: 99%
See 1 more Smart Citation